Planejamento tributário e normas antielisivas: uma análise a partir da perspectiva de nosso sistema constitucional - Teles, Galderise Fernandes (2014)
The present document is the Tax Planning and Anti-Avoidance rules analysis core. In this context, we analyze the existence and compatibility of these standards in our Constitutional Tax System, always arguing for the absence of this relevance regarding our legal system. There are further analyses of the arguments used by the administrative authority for requalification of taxes on legal business, always having na attitude in order to refute any arguments grounded in foreign legislation or not legal foundation. There is, therefore, an effort to achieve a logical and systematic triggering around the theme, adopting and approach of strictly legal tax nature to this aspiration, having in the Constitutional Tax System its greatest grounding validity